Design and Characterization of 5 μm Pitch InGaAs Photodiodes Using In Situ Doping and Shallow Mesa Architecture for SWIR Sensing - Jules Tillement; Cyril Cervera; Jacques Baylet; Christophe Jany; François Nardelli; Thomas Di Rito; Sylvain Georges; Gabriel Mugny; Olivier Saxod; Olivier Gravrand; Thierry Baron; François Roy; et al. (Sensors, 2023)
This paper presents the complete design, fabrication, and characterization of a shallow-mesa photodiode for short-wave infra-red (SWIR) sensing. We characterized and demonstrated photodiodes collecting 1.55 μm photons with a pixel pitch as small as 3 μm. For a 5 μm pixel pitch photodiode, we measured the external quantum efficiency reaching as high as 54%. With substrate removal and an ideal anti-reflective coating, we estimated the internal quantum efficiency as achieving 77% at 1.55 μm. The best measured dark current density reached 5 nA/cm2 at −0.1 V and at 23 °C. The main contributors responsible for this dark current were investigated through the study of its evolution with temperature. We also highlight the importance of passivation with a perimetric contribution analysis and the correlation between MIS capacitance characterization and dark current performance.